Effect of Propolis Extract on Oxidative Stress Biomarker in Diabetic Wistar Rat (Rattus novergicus) - Meida, Nur S.; Purwanto, Bambang; Wasita, Brian; Indrakila, Senyum; Soetrisno, Soetrisno; Poncorini, Eti; Cilmiaty, Risya; Pratiwi, Woro R.; Setyandriana, Yunani; Almahira, Syifa (Faculty of Pharmacy, University of Benin, 2022)
Diabetes mellitus (DM), is a hyperglycemic condition, which increases oxidative stress, thereby leading to complications. One of the biomarkers of oxidative stress is malondialdehyde (MDA), whose levels can be used to predict oxidative stress levels. Propolis, an herbal medicinal plant extensively used to treat a variety of ailments, has been shown to lower oxidative stress. This study was conducted to determine the effect of Gunung Lawu propolis extract on MDA levels in a diabetic rat model. Ethanol extract of Gunung Lawu propolis was prepared and used in the treatment. Twenty-five (25) Wistar rats (Rattus novergicus) were randomly chosen and divided into five groups. The normal (healthy control; K1), DM (positive control; K2), and treatment groups, which consisted of DM rats that received different doses of propolis extract: P1 (100 mg/kg BW after 14 days of induction), P2 (200 mg/kg BW after 14 days of induction), and P3 (200 mg/kg BW immediately after induction). After 28 days, the rats were euthanized, and blood samples were collected and processed into the serum. The levels of MDA in the blood serum samples were measured. The results revealed that propolis significantly reduced fasting blood sugar (p<0.01) and MDA levels (p[removed]0.01) in reducing fasting blood sugar and MDA levels in early (P3) and advanced (P2) diabetes stages. The findings of this study revealed that propolis can lower MDA levels (an oxidative stress biomarker) in diabetic rats, thereby suggesting its potential in managing DM.